Essays in applied and psychological game theory: cooperation, corruption and political economy - Balafoutas, Loukas (The University of Edinburgh, 2009)
The first chapter of the thesis applies game theory in order to examine the question of income redistribution from a fresh angle. In particular, it considers a mechanism of patron-client relationships which enables a society's rich class to limit the extent of redistributive taxation. In effect, the aim of patronage is to "buy" the votes of some poor citizens and lower the demand for redistribution. Income tax rates are further shown to depend negatively on government corruption in the form of fund capture, provided that a democratic regime is in place and the government cares about reelection. This link is tested empirically using cross country data and the evidence is consistent with the predictions of the model.

The second and third chapters shift the focus of attention towards the process of decision making in games and the role of emotions in this process. Corruption, which is taken as exogenous in the first chapter, is now considered in detail as the outcome of a cooperation game between two players, with a third player (or "third party") having a stake in the outcome of the game but no opportunity to take any direct action. This situation is analysed using psychological game theory. Players' utility functions are extended to include beliefs and the emotions that these generate. In the theoretical model of the second chapter the emotion of interest is guilt and this is conditioned on the perceived beliefs of the third party. The two players are then less likely to collude if they believe that the third party expects a favourable outcome for herself. The model solves for the conditions under which collusion emerges in equilibrium. The main assumption of the model (i.e. the role of beliefs in decision making) as well as some of its predictions are then tested using an economic experiment in the third and final chapter of the thesis. The experimental findings strongly support the impact of beliefs on the incidence of collusion: Perceived expectations of the third party about the outcome of the game appear to be the most significant factor that determines the outcome itself. There seems to be a mechanism of self-fulfilling expectations which can be applicable to a number of economic situations, including corruption in public administration.